Myocardial blood flow and adenosine A2A receptors in cross-country skiers expressing remarkable left ventricular hyperthrophy - Heinonen, I.; Nesterov, S.; Liukko, K.; Kemppainen, J.; Nägren, K.; Luotolahti, M.; Virsu, P.; Nuutila P.; Knuuti, J.; Kujala, U.; Kainulainen, H.; Kjaer, M.; et al. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Extreme forms of athlete's heart structurally resemble hypertrofic cardiomyopathy, which is a life-threatening disease associated with reduced myocardial blood flow (MBF) reserve (Camici & Crea 2007). However, it is not known how athlete's heart close to upper extremities (Maron & Pellicia 2006) showing any signs of maladaptive cardiac hypertrophy affects MBF and its reserve, and this was investigated in the present study. Additionally, it was sought to determine whether adenosine A2A receptors, which are regarded as important regulators of MBF, are affected in pronounced athlete's heart.